(untitled) (Agro Productividad, 2024)
Objective: To evaluate the effect of the Supermix bioinput on milpa yield, using local technologies practiced by producers from three communities of the Sierra Nevada. Design/Methodology/Approach: The milpa —a polyculture that consists of maize, beans, and squash— provides a diversity of nutritious foods for families, with production ranges that are constant throughout the region. Applying bioinputs opens the possibility of improving these ranges. The Supermix was applied in five 30-m long rows in 9 producer-managed milpa plots, in order to carry out an exploratory measurement of its effect on the productive levels of the polyculture. For comparative purposes, the average yields of the milpa were estimated, both in the 5 rows in which the Supermix was applied and in the rest of the plot (control). Results: In the three communities under study, the milpa produced in average 2.51 t of maize, 170.6 kg of beans, and 122.9 kg of squash seed per hectare; meanwhile, the control produced 2.57 tons of maize, 159.3 kg of beans, and 99.6 kg of squash seed. The total yield of the milpa system (sum of all products) to which the Supermix was applied was 2,804 kg ha-1, while the control system recorded 2,828 kg ha-1. Study Limitations/Implications: Drought, pest damage, and previous bean harvests influenced the results. Findings/Conclusions: The average yields of beans and squash to which Supermix was applied were higher than with the control, opening opportunities for innovation. Additionally, work in the milpa is mostly carried out by women.